Ultrathin Porous NiFeV Ternary Layer Hydroxide Nanosheets as a Highly Efficient Bifunctional Electrocatalyst for Overall Water Splitting - Dinh, Khang Ngoc (2018)
Herein, the hydrothermal synthesis of porous ultrathin ternary NiFeV layer double hydroxides (LDHs) nanosheets grown on Nickel foam (NF) substrate as a highly efﬁcient electrode toward overall water splitting in alkaline media is reported. The lateral size of the nanosheets is about a few hundreds of nanometers with the thickness of ≈10 nm. Among all molar ratios investigated, the Ni0.75Fe0.125V0.125‐LDHs/NF electrode depicts the optimized performance. It displays an excellent catalytic activity with a modest overpotential of 231 mV for the oxygen evolution reaction (OER) and 125 mV for the hydrogen evolution reaction (HER) in 1.0 m KOH electrolyte. Its exceptional activity is further shown in its small Tafel slope of 39.4 and 62.0 mV dec−1 for OER and HER, respectively. More importantly, remarkable durability and stability are also observed. When used for overall water splitting, the Ni0.75Fe0.125V0.125‐LDHs/NF electrodes require a voltage of only 1.591 V to reach 10 mA cm−2 in alkaline solution. These outstanding performances are mainly attributed to the synergistic effect of the ternary metal system that boosts the intrinsic catalytic activity and active surface area. This work explores a promising way to achieve the optimal inexpensive Ni‐based hydroxide electrocatalyst for overall water splitting.